2014
DOI: 10.1111/aas.12451
|View full text |Cite
|
Sign up to set email alerts
|

The spread of injectate during saphenous nerve block at the adductor canal: a cadaver study

Abstract: Injection of 15 ml dye was sufficient to spread throughout the adductor canal and beyond both proximally and distally. Distinct ultrasonographic features could be identified separating a subsartorial injection from an injection within the adductor canal with consequent differences in the spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
83
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 15 publications
4
83
0
1
Order By: Relevance
“…Similar to prior studies, we elected to use unembalmed cadavers to prevent alterations in the tissue characteristics by embalming process 24. Position of the needle tip in relation to the omohyoid muscle and its investing fascia is pivotal.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior studies, we elected to use unembalmed cadavers to prevent alterations in the tissue characteristics by embalming process 24. Position of the needle tip in relation to the omohyoid muscle and its investing fascia is pivotal.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a spread of injectate to the popliteal fossa after injection into the AC, but none of these studies have assessed whether the injectate reached the popliteal plexus and the genicular branch of the posterior obturator nerve. [15][16][17][18] The latter plays an important clinical role in knee pain after TKA. 3,19,20 The obturator nerve can be anesthetized by an ultrasound-guided subpectineal injection of local anesthetic at the level of the inguinal crease.…”
Section: Discussionmentioning
confidence: 99%
“…11,24 The medial retinacular nerve from the medial vastus nerve dives into a fascial tunnel proximal to the entrance of the AC between the medial vastus muscle and the adductor longus muscle outside the AC in 90% of human subjects. 25 In the remaining 10%, the nerve is superficial to the medial vastus muscle fascia and descends inside the AC. The medial retinacular nerve lies adjacent to the medial recurrent geniculate artery and vein and runs deep to the medial retinaculum after it emerges from the inferior margin of the medial vastus muscle.…”
Section: Blockade Of Femoral Nerve Branches Inside and Around The Acmentioning
confidence: 99%
“…The medial vastus nerve lies deep to the sartorius muscle and superficial to the roof of the AC, outside the AC. 25,27 We have performed dissections of the AC in 4 cadavers at the Division of Clinical and Functional Anatomy, Medical University of Innsbruck, Austria, to solve this paradox. All 8 dissections showed that the medial vastus nerve lies outside the AC in a separate fascial tunnel on the medial vastus muscle (Fig.…”
Section: Blockade Of Femoral Nerve Branches Inside and Around The Acmentioning
confidence: 99%